Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
First we already know x, so we can put it into the other equation like so:
3(3y+7)-4y=16
Then we can solve it.
9y+21-4y=16
5y=-5
y=-1
Then we can find x.
x=3y+7
x=3(-1)+7
x=-3+7
x=4
Hope I helped!
3(3y+7)-4y=16
Then we can solve it.
9y+21-4y=16
5y=-5
y=-1
Then we can find x.
x=3y+7
x=3(-1)+7
x=-3+7
x=4
Hope I helped!
x = 3y + 7
3x - 4y = 16
Substituting the value of x,
3(3y + 7) - 4y = 16
9y + 21 - 4y = 16
5y + 21 = 16
5y = -5
Thus, y = -1.
Substituting the value of y,
x = 3y + 7
x = -3 + 7
Thus, x = 4.
Thus, x = 4, and y = -1
3x - 4y = 16
Substituting the value of x,
3(3y + 7) - 4y = 16
9y + 21 - 4y = 16
5y + 21 = 16
5y = -5
Thus, y = -1.
Substituting the value of y,
x = 3y + 7
x = -3 + 7
Thus, x = 4.
Thus, x = 4, and y = -1
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.